2007
DOI: 10.1534/genetics.107.081976
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Spt3 and TATA-Binding Protein Mutants of Saccharomyces cerevisiae: Spt3–TBP Allele-Specific Interactions and Bypass of Spt8

Abstract: The Spt-Ada-Gcn5-acetyltransferase (SAGA) complex of Saccharomyces cerevisiae is a multifunctional coactivator complex that has been shown to regulate transcription by distinct mechanisms. Previous results have shown that the Spt3 and Spt8 components of SAGA regulate initiation of transcription of particular genes by controlling the level of TATA-binding protein (TBP/Spt15) associated with the TATA box. While biochemical evidence exists for direct Spt8-TBP interactions, similar evidence for Spt3-TBP interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 63 publications
(86 reference statements)
4
44
1
Order By: Relevance
“…Individual cells appear as budded or filamentous cells (37). The ability to switch among these morphologies is required for C. albicans pathogenicity (38,39), suggesting that multiple morphologies contribute to host infection. Filamentous growth can be triggered by various stimuli, including oxidative stress (40), activation of the DNA damage, and replication checkpoints due to exogenous or endogenous DNA damage (41,42), or by cell-cycle delays resulting from perturbed microtubule dynamics or spindle checkpoint activation (43,44; reviewed in ref.…”
Section: Resultsmentioning
confidence: 99%
“…Individual cells appear as budded or filamentous cells (37). The ability to switch among these morphologies is required for C. albicans pathogenicity (38,39), suggesting that multiple morphologies contribute to host infection. Filamentous growth can be triggered by various stimuli, including oxidative stress (40), activation of the DNA damage, and replication checkpoints due to exogenous or endogenous DNA damage (41,42), or by cell-cycle delays resulting from perturbed microtubule dynamics or spindle checkpoint activation (43,44; reviewed in ref.…”
Section: Resultsmentioning
confidence: 99%
“…TFIID stably binds TBP under certain conditions, while purified SAGA contains little TBP (Sterner et al 1999;Sanders et al 2002;Laprade et al 2007). Genetic and biochemical studies implicate the subunits Spt3 and Spt8 in TBP binding.…”
Section: Saga Organization and Tbp Bindingmentioning
confidence: 99%
“…Genetic and biochemical studies implicate the subunits Spt3 and Spt8 in TBP binding. These Spt subunits genetically interact with TBP, and mutations in Spt3 can suppress TBP mutations (Eisenmann et al 1992(Eisenmann et al , 1994Laprade et al 2007). In one case, an Spt3 mutation was found to dramatically increase the amount of TBP copurifying with SAGA (Laprade et al 2007).…”
Section: Saga Organization and Tbp Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in different eukaryotes have suggested that the presence of SAGA at the promoters of genes is needed to facilitate Pol II recruitment and pre‐initiation complex (PIC) formation (Wyce et al , 2007; Nagy et al , 2009; Helmlinger et al , 2011; Lang et al , 2011). The recruitment of SAGA and ATAC coactivator complexes to genomic loci has been suggested to take place by several distinct mechanisms: (i) by activator mediated recruitment (McMahon et al , 1998; Brown et al , 2001; Fishburn et al , 2005; Reeves & Hahn, 2005), (ii) by interactions with basal transcription machinery components (Larschan & Winston, 2001; Laprade et al , 2007; Mohibullah & Hahn, 2008) and (iii) through chromatin‐interacting domains of SAGA and ATAC subunits (Hassan et al , 2002; Vermeulen et al , 2010; Bian et al , 2011; Bonnet et al , 2014). Nevertheless, the dynamics of SAGA and ATAC interactions with chromatin are not yet well understood, as there has been no direct and systematic monitoring of the nuclear mobility of these two co‐activator complexes in live cells.…”
Section: Introductionmentioning
confidence: 99%